Metodologia de manutenção preditiva para motores elétricos baseada em monitoramento de variáveis físicas e análise multicritério - Leme, Murilo Oliveira (2017)
This work presents the development of a predictive maintenance methodology for electric motors, which uses the variable monitoring technique, data transmission through the electric network (Powerline Communication) and a treatment with multicriteria methods for sorting (ELECTRE TRI and AHPSort) and ranking (ELECTRE II) electric motors with incipient failure condition and the use of existing electrical installations for the acquisition of data of the operation of electric motors such as voltage, current, temperature and vibration. This information can be evaluated and treated through multicriteria methods to allocate motors in classes that represent normal, acceptable, and incipient failure states. Thus, in electric motors classified as incipient failure condition, a ranking can be performed to detect the engine in the worst operating state. In this work, a bench experiment was conducted with a 1-minute acquisition period of the operating variables in 6 motors. In this period, the electric motor can be registered that presented the most critical conditions for the fault, considering the measured variables as criteria in the analysis. After a longer period of analysis, we computed every time this engine was classified in the incipiente failure and first rank class, which means that it has conditions that are out of the normal operating range and worse than the other engines analyzed. Through this methodology it is possible to indicate to the maintenance manager deviations from the normal operation of electric motors, considering more than one variable at the same time aligned to the objectives of the decision maker, through the weights calculated for the criteria and limits and preferences established in each multicriteria method used in the methodology proposed in this work.